Evaluation of Cost-Benefit and Measures During the COVID-19 Pandemic for Incoming Travelers Through Tests in Origin in Spain - Domínguez, Conrado; García, Rubén; Sánchez, Javier; Suárez, José Pablo; Dávila-Quintana, Carmen Delia (Frontiers in Public Health, 2022)
Background The World Health Organization has promoted preventive measures for reducing the impact of the pandemic. One of these measures was tests in origin for travelers. Testing strategies for COVID-19 facilitate the overall public health response to the pandemic and contributes to minimize the infection among the population COVID-19. Goal In this work, we assess the efficiency of diagnostic testing of incoming travelers in the Canary Islands, Spain, during a period of 4 months, with a focus on the economic impact for the regional government. We study the cost-benefit of this measure as well as the potential influence on the number of positive cases in the population. Methods We processed the real data in the Canary Islands of pre-flight PCR and antigen tests that were required to the residents when traveling back to the Canaries from anywhere in Spain in a period of 4 months, from 14 December, 2020 to 4 April, 2021. As a result, we calculated the economic impact of doing those tests and compare them with the estimated costs of passengers under the hypothesis of entering the islands without testing. The cost-benefit was obtained for different scenarios, where the incoming passengers generated hospitalization and intensive care unit (ICU) costs directly and via transmissions. Results The incoming testing funded by the government, if applied during the bad evolution of the pandemic with 1.2 ratio of transmission, clearly saved money to the public health system. In addition to the economic impact of this measure, we estimated the potential influence on the number of positive cases in the population according to different scenarios of the propagation of the pandemic. At the beginning of February 2021, the savings were about €130.551,47, with a 95% confidence interval (CI) of €24.677,94–236.425,00. By the end of April 2021, the savings were above €2,000,000 (€2.284.788,50 on average and 95% CI of €2.092.914,84–2.476.662,16) and the savings increased as the pandemic evolved. At the end of the period, the savings were twice the expenses. Conclusions Testing in origin has proved to be a good measure that helped to mitigate COVID-19 spread among regions. Our results confirm that the free PCR or rapid antigen tests produce relevant savings to the public budget. We studied 61.990 reported data during 2020 and 2021 from the travelers from national flights, against 346.449 of total incoming travelers to the Canary Islands in this period. The measure pursued by the Government of the Canary Islands of providing free tests for residents showed a clear benefit for both, limiting the propagation of COVID-19 and reducing the costs of the hospitalizations and ICU admissions. It should be noted that the free testing measure in this period was before starting the vaccination campaigns. As measure of public health in the airports, testing helped to control and make the mobility of travelers secure.